A 1000 fps High-Dynamic-Range Global Shutter CMOS Image Sensor with Full Thermometer Code Current-Steering Ramp - Liqiang Han; Ganlin Cheng; Xu Zhang; Gengyun Wang; Weijun Pan; Yao Yao; Guihai Yu; Ruimeng Zhang; Shuaichen Mu; Songbo Wu; Hongbo Bu; Liqun Dai; et al. (Sensors, 2025)
We present a 1024 × 512, 1000 fps, high-dynamic-range global shutter CMOS image sensor. The pixel is based on a voltage domain global shutter architecture, featuring a pitch of 24 μm × 24 μm. Both high-gain and low-gain signals can be captured within a single frame. The combined dynamic range is 95 dB, and the full well capacity is 620 ke-. In this paper, we analyze the pixel noise performance as well as the non-linearity and image lag that arise from parasitic capacitance in the pixel. The ramp generator is based on a 12-bit full thermometer code current-steering DAC with high driving capability. We discuss the design considerations for the ramp generator, particularly addressing the phenomenon of non-linear response. Finally, the comparator design and the column readout noise are analyzed.